HUBUNGAN DUKUNGAN KELUARGA DENGAN SIKAP IBU HAMIL DALAM PEMANFAATAN ANC DI WILAYAH KERJA PUSKESMAS PEGIRIAN KOTA SURABAYA - Mardahlia, Dewi; Johan, Herni (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2019)
The coverage of pregnant women visit K4 in Surabaya for 2016 amounting to98.48%, the percentage is not far SPM targets have been set. This study was conducted inorder to determine the relationship of family support with the attitude of pregnant womenin antenatal care pemanfaartan Pegirian Puskesmas working area of Surabaya. Theresearch type is descriptive analytic with cross sectional approach or cross sectional. Thestudy was conducted in October-November 2017 in Pegirian PHC Surabaya. Thepopulation in this research that all pregnant women in the Puskesmas Peggirian.Sampling is by accidental sampling that 64 pregnant women who visited the health centerPegirian Surabaya. Data collected through interviews with the questionnaire guide.Analysis of the data that is in univariate and bivariate. The Results:results showed thatout of 64 pregnant women who lack family support but has a good enough attitude that asmany as 1 (100%), pregnant women who have pretty good support and have a prettygood attitude as well as 43 (72.9%). While pregnant women are getting support but theattitude of the mother is not good in 2 (50%). The test results meninjukkan OR sig 0.000and 9.660. there is a significant relationship between family support with the attitude ofpregnant women in antenatal care utilization in Puskesmas Wonokusumo Surabaya